IMPLIKASI BIOLOGI REPRODUKSI TERHADAP KONSERVASI GENETIK JENIS Santalum album - Liliana Baskorowati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
Santalum album is one of the extinct species which need to be conserved. Therefore, the information of reproductive biology of this species, especially the pollination system can produce important clues in order to conserve it. Preliminary study of pollination system of S. album was conducted at ex-situ conservation plot at Watusipat, Gunung Kidul, Yogyakarta. The observations showed that S. album flowers categorised as protandrous, which structured acropetally; this structure may lead self-pollination within a spike. However, result from artificial pollination showed that S. album was a predominantly out crossing species. Very low level of seeds setted from self-pollinated flowers indicated that pollinator was needed for reproduction process. Observation revealed that European honey bee (Apis mellifera) was one of potential pollinating agents.